Andi Arlina, Winda, Dian Factors Related to the Frequency of Sexual Intercourse in Pregnant Women at the Kapasa Health Center in Makassar City in 2023 - Andi Arlina (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2023)
Sexual in pregnancy is an important aspect of health but rarely discussed well. Sexual intercourse can occur during pregnancy, but the frequency varies greatly, a decrease in the frequency and quality of sexual intercourse can give rise to sexual dysfunction that can cause serious problems with the harmony of the husband and wife. The purpose of this study is to determine the factors related to the frequency of sexual relations in pregnant women at the Kapasa Health Center, Makassar City in 2023. This research is an analytical research with a cross-sectional approach. The sample was 24 people with a random sampling technique. Data collection using questionnaire sheets, then analyzed using the Chi-Square Test. The results of the study obtained were that there was a relationship between physical changes and the frequency of sexual intercourse with a p value of 0.000 (<0.05). The second result was a relationship between maternal knowledge and the frequency of sexual intercourse with a p value of 0.029 (<0.05). The third result is a relationship between the work and the frequency of sexual intercourse in pregnant women with a p value of 0.022 (<0.05)